Pengaruh Terapi Asertif Terhadap Kenakalan Remaja - Maryuti, Ira Ayu (JURNAL NERS LENTERA, 2021)
Juvenile delinquency is a condition where a teenager takes an action that ignores social values, so that it can cause harm to himself and the surrounding environment. Neglected juvenile delinquency can lead to criminal acts, so action is needed to overcome juvenile delinquency. The purpose of this study was to determine the effect of therapeutic group therapy on juvenile delinquency. Methods: This study used a quasi-experimental design with a pre and post test design. Sampling using purposive sampling as many as 15 respondents that is in accordance with the inclusion criteria. The intervention was carried out in 5 sessions with a duration of 30-40 minutes per session. The measuring instrument used is a juvenile delinquency questionnaire. The statistical test used to determine the effectiveness of assertive therapy in reducing juvenile delinquency is Wilcoxon. Results: The results of statistical tests using Wilcoxon after the intervention showed p = 0.001 (< 0.005). Discussion: Adolescents who experience conflict with their parents and peers, and are unable to express their attitudes, feelings, opinions, and rights, often commit juvenile delinquency. Assertive therapy aims to teach assertiveness, so that teenagers can express their opinions properly and freely, but politely. Assertiveness is not only seen from what is conveyed verbally, but also nonverbally. Conclusion: There is an effect of therapeutic group therapy on juvenile delinquency.